2022
DOI: 10.21203/rs.3.rs-1952085/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-diabetic and anti-obesity activity of Caralluma adscendens var. gracilis and Caralluma pauciflora

Abstract: The plants fractions of Caralluma adscendens var. gracilis and Caralluma pauciflora were evaluated for their total phenolic content in relation to their antioxidant activity and inhibitory effect of starch and lipids digestive enzymes. Among all fractions of C. adscendens var. gracilis and C. pauciflora, diethyl ether fractions showed highest phenolic content (36.23 ± 1.51 mg of GAE g− 1 DW, 28.21 ± 3.61 mg of GAE g− 1 DW), DPPH radical scavenging activity (27.96 ± 3.45 µg ml− 1 and 37.23 ± 0.92 µg ml− 1), inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies have found that the ethanol and methanol extracts of Caralluma sp. have cytotoxic effects on human cancer cells such as breast cancer, lung cancer, and oral cancer cells [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the ethanol and methanol extracts of Caralluma sp. have cytotoxic effects on human cancer cells such as breast cancer, lung cancer, and oral cancer cells [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%